Geneologi Islamisme di Kalangan Muslim Millenial Indonesia - Moh Dahlan (IAIN Bengkulu, 2020)
In the last decade, Indonesian Millennial Muslims have a tendency to choose Islamism as their life trend, so as it becomes a problem in the life of a plural Indonesian people. By using the ushul fiqh approach, data collection techniques using library research and content analysis techniques, this study shows that first, the genealogy of the paradigm of Islamism that develops in Indonesia does not always have a negative connotation that means radicalism, but the paradigm of Islamism among Millennial Muslims in Indonesia has turned out to be a medium for packaging and spreading the paradigm of popular Islamism. Therefore, there is a correlation between the jargon carriers of Islamism and its products. Second, the birth of the paradigm of Islamism among millennial Muslims occurred because of the existence of culture, learning ethos and social media and electronics that have encouraged the birth of the paradigm of Islamism, so that it has brought a new trend that supports an increasingly massive and popular Islamic life with innovative and creative packaging.Third, the implications of the paradigm of Islamism among Millennial Muslims have had positive and negative impacts.The positive impact is that Islamism encourages millennial Muslim generations to learn, understand and practice the teachings of Islam in a comprehensive manner as well as popular Islamic understanding which is in accordance with maqashid al-shari'ah, while the negative impact is that the encouragement of learning, understanding and practicing religious teachings Islam in a comprehension that is exposed to the understanding of radicalism-intolerant can actually lead to intolerant attitudes and behaviour, even radicalism that is contrary to the Maqashid al-Shari'ah